CULTURAL REPRESENTATIONS IN THE NOVEL (CHICAGO) - Assist. Prof. Ibrahim Mustafa Hamad Khamis, Assist. Lect. Saad Yassin Lateef Akash, Assist. Prof. Abdullah Hassan Jameel Saleh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Ala 'Al Aswani's novel CHICAGO belongs to postmodernist Arabian novels. The study attempts to identify the most important technical and objective issues dealt with in the novel and to reveal the patterns of the novel's discourse. The study falls into an introduction, four chapters and a conclusion which sums up the findings of the study. The study made use of findings of cultural criticism and did not deny the idiomatic and conceptual overlap, which serves and enriches the process of tbe research and makes it more agile in responding to the requirements of the study.